(untitled) (Global Journal of Management and Business Research, 2018)
In this article we review the literature on the relationship between the capitalization requirement and the ability of the bank to withstand a shock. The theoretical literature review reveals a controversy about the relationship between the level of capitalization and bank robustness. On the basis of portfolio selection theory, a binding capitalization requirement can lead to an increase in risk taking. Conversely, the state preference theory argues for the positive effect of the capitalization requirement on bank robustness.